Fenomena Relationship goals TikTok: Analisis Nilai Hubungan dalam QS. Ar-Rum Ayat ke-21 dan Hadits-Hadits Mahabbah - Nikyta Tsabita Khansa; Nasrulloh (Al-Kindi, 2026)
This study aims to analyze the phenomenon of relationship goals on TikTok and its relevance to relationship values in Islam based on QS. ar-Rum verse 21 and mahabbah hadiths. This trend is noticed because many of the younger generation's romantic perceptions are shaped through the appearance of ideal relationships that often emphasize visual and performative aspects more than the reality of the real relationship. The research method uses a qualitative approach based on literature study through the analysis of Islamic literature, communication theory, adolescent psychology, and digital media studies. The results of the study show that the relationship construction on TikTok is not fully aligned with the principles of sakinah, mawaddah, and rahmah, and has the potential to create unrealistic expectations about love and commitment. However, a number of content still has harmony with the values of the Qur'an-Hadith, especially in the aspects of good communication, mutual support, and cooperation in relationships. This research emphasizes the importance of digital literacy based on Islamic ethics so that the younger generation is able to understand relationships more wisely and not get caught up in unrealistic relationship idealization.